Evolution of China’s energy security : the impact of domestic reforms and policies - Yao, Lixia (2014)
Despite unprecedented energy consumption rates and environmental sustainability threats, China has seen fast economic growth in the past 30 years of reform. Within this context, this study applies both quantitative and qualitative analyses to the energy security situation in China between 1980 and 2010.